Effects of Propolis on Selected Blood Indicators and Antioxidant Enzyme Activities in Broilers under Heat Stress - Seven, Pinar Tatli; Yilmaz, Seval; Seven, Ismail; Cerci, Ibrahim H.; Azman, Mehmet A.; Yilmaz, Mehmet (Veterinarni A Farmaceuticka Univerzita Brno, 2009)
In this study, we investigated the antioxidant activity of ethanol extracts of propolis (EEP) and vitamin C on biochemical indicators and antioxidant enzyme activities of broilers exposed to heat stress (at 34 degrees C). The experimental groups were as follows: group I (positive control) and group II (control) were fed a basal diet, group III (vitamin C) was fed a basal diet supplemented with 250 mg vitamin C as ascorbic acid/kg, group IV (EEP-0.5) was fed a basal diet supplemented with 0.5 g EEP/kg, group V (EEP-1) was fed a basal diet supplemented with 1 g EEP/kg, group VI (EEP-3) was fed a basal diet supplemented with 3 g EEP/kg. Plasma superoxide dismutase levels of positive control, control, vitamin C, EEP-0.5, EEP-1 and EEP-3 groups were found as 0.34, 1.23, 0.50, 0.90, 0.30 and 0.41 mu kat/ml, respectively (p < 0.01). Aspartate transaminase (except for EEP-0.5 and EEP-1 groups) and alkaline phosphatase in the control group were significantly higher than those of positive control, vitamin-C and EEP-3 groups. Malondialdehyde level in plasma, liver and muscle tissues of control group were found significantly (p < 0.05) higher than those of positive control and EEP-3 groups. Catalase activities of blood, liver, kidney and heart were the highest in the control group. Reduced glutathione activities of plasma and liver of all groups were not significantly different from each other, whereas those of muscle, kidney and heart were significantly higher in the control group. Significantly lower levels of glutathione peroxidase were found in blood, liver and kidney tissues of the control group (p < 0.05), whereas those of muscle and heart were similar in all groups. The results of the present study suggest that EEP and specially EEP at the supplemented dose of 3 mg/kg diet might be considered to prevent oxidative stress in the broilers exposed to heat stress.
Keywords: Propolis; antioxidant enzymes; blood; heat stress; broilers